Effects of Sequential Antimicrobial Phases on Root Canal Microbiome Dynamics in Two-Visit Treatment of Primary Apical Periodontitis: A Longitudinal Experimental Study - Bertan Kesim; Seda Tezcan Ülger; Gönül Aslan; Yakup Üstün; Ayşe Tuğba Avcı; Mustafa Öner Küçük (Life, 2024)
Background: Effective management of primary apical periodontitis depends on understanding the dynamic interactions within the root canal microbiome. This study aimed to investigate the effect of sequential antimicrobial phases on the root canal microbiome during a two-visit treatment approach, with a focus on calcium hydroxide medication. Methods: Samples were collected from three teeth across four treatment phases: initial infection (S1), after chemomechanical preparation (S2), after intracanal medication (S3), and after a final flush (S4). DNA was extracted, and the V3–V4 regions of the 16S rRNA gene were sequenced using Illumina MiSeq. Sequencing data were analyzed with QIIME 2, and differentially abundant taxa were identified using linear discriminant analysis effect size (LEfSe). Results: While microbial community composition did not differ significantly between phases, the Firmicutes/Bacteroidetes ratio decreased after the antimicrobial stages. LEfSe analysis revealed higher abundances of Lactobacillales, Arthrobacter, and Veillonella in the untreated (CMP) group. Bifidobacterium longum was relatively more abundant in the intracanal medication (ICM) phase, and Dorea formicigenerans was more abundant in the final-flush (FF) phase. Conclusions: Although calcium hydroxide treatment did not induce statistically significant changes in overall root canal microbial composition, trends such as a reduction in the Firmicutes/Bacteroidetes ratio and a relative increase in Bifidobacterium longum numbers suggest potential ecological shifts. The observed relative increase in Bifidobacterium longum numbers may represent a hypothesis-driven observation reflecting indirect ecological effects rather than direct pH modulation. While visual patterns (e.g., PCA clustering) were observed, they lacked statistical support. Further studies with larger sample sizes are needed to validate these observations and assess the potential role of beneficial bacteria in root canal treatments.